2017
DOI: 10.1371/journal.pone.0183910
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin concentration and risk of cardiovascular outcomes in nine general population studies: Literature-based meta-analysis involving 26,442 participants

Abstract: BackgroundRecent experimental and epidemiological studies have suggested that osteoprotegerin, a key regulator in bone metabolism, may be involved in vascular calcification and atherosclerosis. Our aim was to reliably quantify the associations of osteoprotegerin concentration and incidence of first-ever cardiovascular disease outcomes in the general population.MethodsUsing the electronic databases MEDLINE, EMBASE and Web of Science (January 1975 and April 2017, no language restrictions), nine relevant studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
30
0
2
Order By: Relevance
“…We have previously demonstrated in a literature‐based meta‐analysis that osteoprotegerin is associated with incident CVD in people recruited from the general community 16. A combination of findings from 9 general population studies yielded a pooled relative risk for CVD of 1.83 (95% CI, 1.46‐2.30) for a comparison of extreme osteoprotegerin tertiles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously demonstrated in a literature‐based meta‐analysis that osteoprotegerin is associated with incident CVD in people recruited from the general community 16. A combination of findings from 9 general population studies yielded a pooled relative risk for CVD of 1.83 (95% CI, 1.46‐2.30) for a comparison of extreme osteoprotegerin tertiles.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, genetic studies have demonstrated associations of osteoprotegerin gene polymorphisms with CVD 11, 12, 13, 14, 15. In a literature‐based meta‐analysis of 9 general population studies, we recently demonstrated robust positive associations between osteoprotegerin concentration and incident CVD 16. However, it is unclear whether these associations equally apply to high‐risk populations.…”
Section: Introductionmentioning
confidence: 97%
“…Based on previous meta-analyses, we mainly expected to find an association between osteoprotegerin, alkaline phosphatase and CVD risk [ 17 , 31 ]. A recent meta-analysis showed that elevated osteoprotegerin concentration was associated with increased CVD risk in the general population [ 31 ]. Another study showed increased osteoprotegerin levels in patients with PAD compared to patients without PAD in participants with type 2 diabetes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPG has been shown to induce vascular fibrosis in aortic samples of apolipoprotein E knockout (ApoE[−/−]) mice, via transforming growth factor-β1 (TGF-β1), which also mediates OPG release in response to angiotensin II in vascular smooth muscle cells 41 . A recent meta-analysis including a total of 26,442 participants from the general population demonstrated an association between raised baseline serum OPG and an increased risk of incident cardiovascular disease at a mean follow-up of 8.5 years, independent of age and clinically-relevant risk factors 35 .…”
Section: Discussionmentioning
confidence: 99%